Surface functionalization of WS2 fullerene-like nanoparticles - Shahar, Chen (Langmuir : the ACS journal of surfaces and colloids, 2010)
WS(2) belongs to a family of layered metal dichalcogenide compounds that are known to form cylindrical (inorganic nanotubes-INT) and polyhedral nanostructures--onion or nested fullerene-like (IF) particles. The outermost layers of these IF nanoparticles can be peeled under shear stress, thus IF nanoparticles have been studied for their use as solid lubricants. However, the IF nanoparticles tend to agglomerate, presumably because of surface structural defects induced by elastic strain and curvature, a fact that has a deleterious effect on their tribological properties. In the present work, chemical modification of the IF-WS(2) surface with alkyl-silane molecules is reported. The surface-modified IF nanoparticles display improved dispersion in oil-based suspensions. The alkyl-silane coating reduces the IF-WS(2) nanoparticles' tendency to agglomerate and consequently improves the long-term tribological behavior of oil formulated with the IF additive